Direct arterial vascularization of estrogen-induced prolactin-secreting anterior pituitary tumors. - Elias, K A (1984)
The rat anterior pituitary gland (AP) receives all of its blood supply via the hypophyseal portal circulation. We now report, in rats with estradiol (E2)-induced prolactin-secreting tumors, that newly formed arteries directly supply the AP and that this arteriogenesis is closely correlated with the sensitivity of two strains of rats to the tumorigenic action of E2. Fischer 344 rats, a strain extremely sensitive to E2, and Sprague-Dawley rats, a less sensitive strain, were ovariectomized and implanted with E2-filled or empty Silastic capsules. Ten to 63 days later, microspheres (15 microns) were injected into the heart. Normally microspheres do not reach the AP because they are trapped in the primary portal capillary plexus. Some animals were also perfused with vascular cast material. In Fischer rats, after 63 days of E2, the pituitary weight, serum prolactin, and number of microspheres in the AP were 5-, 42-, and 18-fold greater than control values, respectively. The same parameters in E2-treated Sprague-Dawley rats were 2-, 27-, and 7-fold greater than control values. Vascular casts from E2-treated Fischer rats revealed numerous arteries entering the AP. No arteries to the AP were observed in Sprague-Dawley controls. These results show that E2-induced tumorigenesis of the AP is associated with the development of a direct arterial blood supply. We hypothesize that the regions supplied by these new arteries would receive systemic blood containing subphysiological concentrations of dopamine. The loss of dopaminergic inhibition in concert with E2 stimulation may lead to tumor formation.